2008
DOI: 10.1177/0363546508316281
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Analysis of Specific Exercises for Scapular Control in Early Phases of Shoulder Rehabilitation

Abstract: These exercises can be used as part of a comprehensive rehabilitation program for restoration of shoulder function. They activate the serratus anterior and lower trapezius-key muscles in dynamic shoulder control-while variably activating the upper trapezius. Activation patterns depended on scapular position resulting in variability of amplitude and activation sequencing between exercises. Inferior glide and low row can be performed early in rehabilitation because of their limited range of motion, while lawnmow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
2
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(204 citation statements)
references
References 51 publications
8
186
2
8
Order By: Relevance
“…14,18,19 Therefore, it is important that these exercises are performed pain free by adjusting humeral elevation angle and resistance. On the other hand, previous studies 30,38 have reported no difference in muscle activity between symptomatic and asymptomatic individuals during performance of the therapeutic exercises. Therefore, retraction exercises may still be viable to potentially improve scapular movements in patients, although further investigation is required to demonstrate this effect.…”
Section: Discussion Tmentioning
confidence: 66%
See 2 more Smart Citations
“…14,18,19 Therefore, it is important that these exercises are performed pain free by adjusting humeral elevation angle and resistance. On the other hand, previous studies 30,38 have reported no difference in muscle activity between symptomatic and asymptomatic individuals during performance of the therapeutic exercises. Therefore, retraction exercises may still be viable to potentially improve scapular movements in patients, although further investigation is required to demonstrate this effect.…”
Section: Discussion Tmentioning
confidence: 66%
“…The upper, middle, and lower trapezius and serratus anterior muscles highly influence the scapular movement through its broad attachments. 3,5,8,10,11,23,30,37,38,46 These muscles are also located superficially, allowing examination of the muscle activity using surface EMG electrodes.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface Electromyography (sEMG) provides a safe, easy and non-invasive method to quantify the energy of the muscles [1]: for these reasons sEMG is currently becoming more and more a powerful tool for the assessment in sport [2], [3], rehabilitation [4], [5], ergonomic design [6], [7], and medical robotics [8].…”
Section: Introductionmentioning
confidence: 99%
“…The target muscles were the pectoralis major and posterior deltoid, as the GHJ muscles, and the middle and lower trapezius and serratus anterior, as the STJ muscles on the dominant side. The EMG electrode position was set according to previous studies by Basmajian et al [19] and Kibler et al [20] .…”
Section: Methodsmentioning
confidence: 99%